Biosociology and neurosociology - Kalkhoff, Will; Thye, Shane R.; Lawler, Edward J. (Emerald, 2012)
This special volume features contributions aligned with the interdisciplinary explosion of research on the biological and neurological foundations of social behavior and organization. Biosociology and neurosociology are rapidly developing scientific fields that draw from, and contribute unique knowledge to, a number of interdisciplinary partners, including: biopsychology, neuropsychology, evolutionary psychology, social and affective neuroscience and neurophilosophy. The chapters in this volume focus on the complex and dynamic links between brain, mind, self, society, and human evolutionary heritage in relation to group dynamics and social interaction, emotions, morality, historical processes, anti-social behavior, and mental health.
Keywords: Neurosciences -- Social aspects.; Biology -- Social aspects.; Interpersonal relations.; elektronické knihy; electronic books